2013
DOI: 10.1002/chem.201302862
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Friedel–Crafts Benzylation with Benzyl TMS Ethers at Room Temperature

Abstract: Friedel-Crafts benzylations between unactivated arenes and benzyl alcohol derivatives are clean and straightforward processes to construct biologically useful di- and tri-arylmethanes. We have established an efficient iron-catalyzed Friedel-Crafts benzylation method at room temperature that uses benzyl TMS ethers as substrates, which are poorly reactive under common nucleophilic substitution conditions. The reaction seems to progress through iron-catalyzed self-condensation of the benzyl TMS ether to the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…(R)-2-Fluoro-4-methoxy-1-(1-phenylethyl)benzene (3ap). 34 Prepared according to the general procedure from styrene 1a (26.0 mg, 0.25 mmol) and 3,4-methylenedioxyphenylboronic acid 2p (85.0 mg, 0.5 mmol). 3ap was isolated in high purity without further purification as a colorless oil in 85% yield (48.9 mg, 0.21 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…(R)-2-Fluoro-4-methoxy-1-(1-phenylethyl)benzene (3ap). 34 Prepared according to the general procedure from styrene 1a (26.0 mg, 0.25 mmol) and 3,4-methylenedioxyphenylboronic acid 2p (85.0 mg, 0.5 mmol). 3ap was isolated in high purity without further purification as a colorless oil in 85% yield (48.9 mg, 0.21 mmol).…”
Section: Methodsmentioning
confidence: 99%
“…Reactions using inexpensive and versatile iron catalysts are accompanied by the generation of neutral waste materials, such as methanol, and are therefore regarded as clean. Recently, we revealed that FeCl 3 efficiently activates various benzylic positions, and several FeCl 3 ‐catalyzed transformations including Friedel–Crafts reactions,,, were reported. Methyl ethers derived from secondary and tertiary benzylic alcohols were also effectively activated by FeCl 3 to generate benzylic cation intermediates, via elimination of the methoxy group, which were coupled with nucleophiles, such as an azide ion, allylic moiety, or cyanide ion .…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13] We have continuously investigated the iron [14][15][16][17][18][19][20] -or gold [21][22][23] -catalyzed activation at the benzylic position of various skeletons accompanied by the benzylic C-O bond cleavage. During these investigations, the benzylic position of phthalan (1; n=1) as a benzene fused cyclic ether was found to be directly azidated in the presence of a gold catalyst and trimethylsilylazide (TMSN 3 ) without the C-O bond cleavage to give the 1-azido phthalan (2) (Chart 1).…”
Section: Gold-catalyzed Benzylicmentioning
confidence: 99%